Legal Empowering the Saniri: A Pillar of Harmony in Post-Conflict Ambon - Nalesti Dewi, Yustina Trihoni; Pandiangan, Andreas; Kwik, Jonathan; Pariela, Tonny Donald; Watloly, Aholiab; Wakano, Abidin; Sanjaya, Andreas Ryan (Udayana Journal of Law and Culture; Vol 8 No 1 (2024)DO - 10.24843/UJLC.2024.v08.i01.p03, 2024)
Due to the lasting impact of the previous authoritarian system, decentralization has yet to reinstate Ambon's customary law-based governance model fully. However, it was formally acknowledged by the national and Ambon City's regional legislation. This article examines the need to empower Saniri, a quasi-governmental body in a traditional village with close ties to underprivileged groups, in conflict resolution services in Ambon. Data was collected through a literature study of historical sources from the nineteenth century and then analyzed based on qualitative field research. Extensive interviews were conducted based on snowball and purposive samplings. Results from the field study were subsequently discovered and deliberated through Focus Group Discussions. It suggests that the current political landscape is permissive to empower Saniri in conflict resolution mechanisms. Therefore, the legal and political efforts must be sufficient to accommodate Saniri's character and support its contribution to post-conflict reconciliation. More attention is required to empower Saniri legally and politically in a manner consistent with its nature to maximize its role as a harmonizing medium.